The Values Of Islam Nusantara’s Civilization And Religious Moderation In Lampungnese Culture Community - Kusuma, Nurhadi; Pepilina, Dini (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2024)
Islam Nusantara is a form of Islam that developed in Indonesia with the characteristics of friendly, tolerant, and mutual respect, in accordance with the identity and character of the people of the archipelago. As a manifestation of the spirit of spreading Islam, Islam Nusantara is integrated with local culture to unite religious teachings and indigenous local wisdom. The transformation and relationship between religion and culture creates the distinctiveness of each locality, as seen in the ethnic culture of Lampung. The relationship between Islam and Lampung culture influences each other, where Islamic values enrich Lampung culture, and vice versa. The people of Lampung express religious moderation as a cultural value that bridges religious diversity in Indonesia. This moderation reflects the harmony between Islam Nusantara and local wisdom, where both do not negate each other, but seek solutions with tolerance. Understanding the values of Nusantara Islamic civilization and religious moderation in the indigenous people of coastal Lampung is an explanation of the relationship between Islam and culture in the development of Lampung society.